Health Economic Evaluation of Patients With Colorectal Liver Metastases Randomized to ALPPS or TSH: Analysis From the LIGRO Trial - Kristina Hasselgren, MD, PhD; Martin Henriksson, PhD; Bård I. Røsok, MD, PhD; Peter N. Larsen, MD, PhD; Ernesto Sparrelid, MD, PhD; Gert Lindell, MD, PhD; Nicolai A. Schultz, MD, PhD; Bjorn A. Bjørnbeth, MD, PhD; Bengt Isaksson, MD, PhD; Magnus Rizell, MD, PhD; Anna Lindhoff Larsson, RN; Per Sandström, MD, PhD; et al. (Annals of Surgery Open)
Objective:. This is a preplanned, health economic evaluation from the LIGRO trial. One hundred patients with colorectal liver metastases (CRLM) and standardized future liver remnant <30% were randomized to associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) or two-staged hepatectomy (TSH). Summary Background Data:. TSH, is an established method in advanced CRLM. ALPPS has emerged providing improved resection rate and survival. The health care costs and health outcomes, combining health-related quality of life (HRQoL) and survival into quality-adjusted life years (QALYs), of ALPPS and TSH have not previously been evaluated and compared. Methods:. Costs and QALYs were compared from treatment start up to 2 years. Costs are estimated from resource use, including all surgical interventions, length of stay after interventions, diagnostic procedures and chemotherapy, and applying Swedish unit costs. QALYs were estimated by combining survival and HRQoL data, the latter being assessed with EQ-5D 3L. Estimated costs and QALYs for each treatment strategy were combined into an incremental cost-effectiveness ratio (ICER). Nonparametric bootstrapping was used to assess the joint distribution of incremental costs and QALYs. Results:. The mean cost difference between ALPPS and TSH was 12,662€, [95% confidence interval (CI): −10,728–36,051; P = 0.283]. Corresponding mean difference in life years and QALYs was 0.1296 (95% CI: −0.12–0.38; P = 0.314) and 0.1285 (95% CI: −0.11–0.36; P = 0.28), respectively. The ICER was 93,186 and 92,414 for QALYs and life years as outcomes, respectively. Conclusions:. Based on the 2-year data, the cost-effectiveness of ALPPS is uncertain. Further research, exploring cost and health outcomes beyond 2 years is needed.